PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN KARAKTER EKSEKUTIF TERHADAP TAX AVOIDANCE - Noorica, Famela; asalam, ardan gani (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study is to simultaneously determine institutional ownership, managerial ownership, executive character of tax avoidance in consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The object of this research is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) with a five-year research period from 2015 – 2019. The sample collection technique in this study uses purposive sampling. The number of samples studied were 70 samples. The implementation time used in this research is panel data, carried out by several stages of testing. The results show that institutional ownership, managerial ownership, and executive character simultaneously affect tax avoidance. Institutional ownership, managerial ownership, and executive character partially affect tax avoidance.